Implementation of Green City Surabaya: Overcoming Challenges of Local-Global and Green Capitalism Development - Siti Aminah (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2022)
Green city is not merely an approach to achieving Sustainable Development Goals (SDGs). Instead, green city is a condition that should preexist to achieve the SDGs. Nevertheless, in many cases, there are gaps in the implementation of green city policies. Therefore, this study aims to evaluate the implementation of green city policy in Surabaya regarding the extent to which this development model has supported the realization of the SDGs set by the United Nations (UN). To answer the research questions, this study uses qualitative methods. Meanwhile, the data collection methods used were in-depth interviews, direct observation, and document analysis. Data analysis was conducted using interpretive methods and thematic analysis, and the perspective used for this study is urban politics. This study eventually finds that implementing the green city policy has supported the achievement of the SDGs in Surabaya, even though it still has many shortcomings. The implementation of a green city has also resulted in the transformation of Surabaya into a modern city that prepares investors and developers to produce the sustainability and feasibility of Surabaya as a pro-environmental city. However, this study also discovers that in order to fully realize a sustainable, humane, and civilized green city, Surabaya still needs to conduct better coordination and collaboration between stakeholders and all elements of society. Keywords: green city, SDGs, Surabaya, urban politics, green capitalism Green city bukan sekadar pendekatan untuk mencapai Sustainable Development Goals (SDGs) atau tujuan pembangunan berkelanjutan. Alih-alih, green city merupakan sebuah kondisi yang harus lebih dulu ada untuk mencapai SDGs. Namun, sering kali terdapat kekosongan dalam implementasi green city. Oleh karenanya, kajian ini hendak mengevaluasi penerapan green city di Kota Surabaya terkait sejauh mana model pembangunan tersebut dapat mendukung pencapaian SDGs yang ditetapkan oleh Perserikatan Bangsa Bangsa (PBB). Untuk menjawab pertanyaan penelitian, penelitian ini menggunakan metode kualitatif. Sementara itu, metode pengumpulan data yang dipakai adalah wawancara mendalam, observasi langsung dan analisis dokumen. Analisis data menerapkan metode interpretif dan analisis tematik, serta perspektif yang digunakan adalah urban politics. Adapun hasil kajian menunjukkan bahwa walau masih memiliki banyak kekurangan, implementasi green city telah mendukung pencapaian SDGs di Surabaya. Implementasi green city juga telah menghasilkan transformasi Surabaya sebagai kota modern yang menyiapkan para investor atau pengembang juga menjadi pelaku untuk memproduksi keberlanjutan dan kelayakan Surabaya sebagai kota yang pro lingkungan. Namun, agar green city yang berkelanjutan, manusiawi, dan beradab sepenuhnya terwujud di Surabaya, masih diperlukan koordinasi dan kolaborasi yang lebih baik antarpemangku kebijakan dan semua elemen masyarakat. Kata-kata kunci: green city, SDGs, Kota Surabaya, politik perkotaan, kapitalisme hijau.